MENINGKATKAN KEMAMPUAN MEMBACA KALIMAT SEDERHANA BAGI ANAK LOW VISION MELALUI MEDIA KARTU KATA - Yamir - Nurta (Jurnal Penelitian Pendidikan Khusus, 2013)
The purpose of this study is: aims to determine the effectiveness of the use of media cards increase the ability to read words in simple sentences for low vision children in the class II SDLB Blind Payakumbuh.This research approach Reaserch Single Subject (SSR) in a design with low vision AB (X). Target size their behavior is "value" in a child's ability to read a simple sentence 10 that have been provided. Condition A (baseline), ie before the given actions and conditions B (intervention) the circumstances in which children are given the intervention through the media card says. Data collected directly by recording the results of tests conducted verbally. Then the obtained data is processed in the graph. The results of this study indicate that the ability to read simple sentences children increased after administration says media card. This is evident in the baseline phase (A) with seven observed to the highest values ​​obtained son is (3). Meanwhile, after a given intervention (B) through the medium of word cards done seven times, the value of the ability of children reached (10), that have all the words the child can read clearly and completely. It can be concluded that the media card is effective words and phrases to improve the ability to read a simple children with low vision. It is suggested that teachers and researchers to use the media card further improve their word reading simple sentences children with low vision.